RESPIRATORY KINESITHERAPY IN CRITICALLY ILL PATIENTS WITH COVID-19: THE REHABILITATION NURSE'S INTERVENTION - CASE STUDY - Marco Fernando Neves China; Helena Isabel Bacalhau Antunes; Lúcia Maria Simões Martins; Maria de Fátima Alves Pereira Ferreira; Maria Fernanda Jesus Simões Viseu; Maria Helena Dias Pires (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Aim: This study aims to describe rehabilitation nurse interventions in Respiratory Kinesitherapy in critically ill with COVID-19 patient undergoing venovenous extra-corporeal membrane oxygenation and its response concerning to gasometric and ventilatory parameters before and after each session. Methodology: Case study of a 63-year-old person with history of obesity and high blood pressure. Retrospective data were collected from the clinical process, referring to a 38-day ICU stay. Results: The most performed techniques used in Respiratory Kinesitherapy by rehabilitation nurses were suctioning through closed system, vibrations, sudden decompression, selective costal openings, forced manual expiration, directed ventilation and mechanical in-exhaler. Globally, all sessions showed that there was an improvement in inspiratory and expiratory volumes, as well as in static compliance. Machanical in-exhaler was used after a week of hospital stay, after all other possible interventions were performed, and all outcomes showed global improvements, without any adverse events. Conclusion: Implementation of structured and individualized respiratory kinesitherapy interventions can significantly benefit recovery of critical ill patients. Techniques that weren´t described for covid 19 cases were used effectively.